Pelatihan Teknik Permainan Konsentrasi pada Guru Sekolah Dasar Muhammadiyah Pahandut Palangka Raya - Misyanto Misyanto; Agung Riadin; Dwi Sari Usop (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
Concentration is an important aspect of mastering the material. Especially for students in elementary school. The age that is still very young, active, and enjoying to play, will have difficulty in understanding the subject material when they lack concentration. Understanding lessons at school experiences ease when combined with the game. The concentration game technique training for Muhammadiyah Elementary School teachers in Palangka Raya aims to develop knowledge and skills for teachers to combine games with lessons so that they can produce meaningful learning.